1988
DOI: 10.1152/ajprenal.1988.254.4.f582
|View full text |Cite
|
Sign up to set email alerts
|

Renin and angiotensinogen gene expression in maturing rat kidney

Abstract: To determine whether angiotensinogen (Ao) and renin are synthesized by the immature kidney and to assess the changes in intrarenal renin distribution that occur with maturation, the kidneys from 24 newborn and 12 adult Wistar-Kyoto (WKY) and spontaneously hypertensive rats (SHR) were processed for renin immunocytochemistry using a highly specific anti-rat renin antibody. Kidney renin and Ao relative mRNA levels (mRNA/total RNA) were detected by Northern and dot blot techniques, using full-length rat renin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
56
1
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 15 publications
9
56
1
1
Order By: Relevance
“…Our understanding of the RAS in normal and pathophysiological regulation of blood pressure has been complicated by the fact that in addition to its actions as an endocrine system, certain individual tissues, such as the kidney (5-7), heart (8, 9), brain (10), and vasculature (11), contain all the components of the RAS cascade and therefore have the potential for local synthesis and action of Ang-II. In the kidney, for example, renin, AGT and ACE mRNAs, and proteins are synthesized in juxtaglomerular cells, proximal convoluted tubule (PCT) cells, and endothelial and tubular cells, respectively, and Ang-II type-1 (AT-1) and type-2 (AT-2) receptors are localized in glomeruli, collecting ducts, tubules, and vasa recta (12)(13)(14)(15)(16)(17)(18). The intrarenal RAS has been postulated to regulate various aspects of renal function including blood flow, natriuresis, and tubular-glomerular feedback, and may therefore participate in the pathogenesis of hypertension (19 -21).…”
mentioning
confidence: 99%
“…Our understanding of the RAS in normal and pathophysiological regulation of blood pressure has been complicated by the fact that in addition to its actions as an endocrine system, certain individual tissues, such as the kidney (5-7), heart (8, 9), brain (10), and vasculature (11), contain all the components of the RAS cascade and therefore have the potential for local synthesis and action of Ang-II. In the kidney, for example, renin, AGT and ACE mRNAs, and proteins are synthesized in juxtaglomerular cells, proximal convoluted tubule (PCT) cells, and endothelial and tubular cells, respectively, and Ang-II type-1 (AT-1) and type-2 (AT-2) receptors are localized in glomeruli, collecting ducts, tubules, and vasa recta (12)(13)(14)(15)(16)(17)(18). The intrarenal RAS has been postulated to regulate various aspects of renal function including blood flow, natriuresis, and tubular-glomerular feedback, and may therefore participate in the pathogenesis of hypertension (19 -21).…”
mentioning
confidence: 99%
“…Ang Ⅱ also acts through intracellular receptors. Local RAS was first described within the kidney over 20 years ago [29][30][31][32] , where the levels of Ang Ⅱ are much higher than in plasma [32,72] . Intrarenal Ang Ⅱ levels and local formation in the kidney have been reported by Navar and colleagues [11,32,[73][74][75][76] .…”
Section: Breaking Paradigmsmentioning
confidence: 99%
“…It is now considered that RAS assumes paracrine, autocrine and intracrine mechanisms of action in hormone signaling [6,28] . Many tissues and cells, including kidneys, have all the necessary RAS components to form Ang Ⅱ in situ [29][30][31] . Renal levels of Ang Ⅱ are much higher than in the plasma [32] , indicating that the source of Ang Ⅱ within the kidney is not only provided by filtered plasma Ang Ⅱ.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The intrarenal expression of renin, angiotensin-converting enzyme, and angiotensinogen mRNAs has been demonstrated by Northern blot analysis (1-6, 14), and the intrarenal tissue sites of renin and angiotensinogen mRNA synthesis have been localized by in situ hybridization (15)(16)(17) . Furthermore, studies using reverse transcription and polymerase chain reaction (RT-PCR) have shown the localization of angiotensin II type 1 receptor and angiotensinogen mRNA in microdissected nephron segments (18).…”
mentioning
confidence: 99%